Housing Code Violation Density Associated With Emergency Department And Hospital Use By Children With Asthma - Beck, Andrew F. (Health Aff (Millwood), 2014)
Local agencies that enforce housing policies can partner with the health care system to target pediatric asthma care. These agencies retain data that can be used to pinpoint potential clusters of high asthma morbidity. We sought to assess whether the density of housing code violations in census tracts—the in-tract asthma-relevant violations (such as the presence of mold or cockroaches) divided by the number of housing units—was associated with population-level asthma morbidity and could be used to predict a hospitalized patient’s risk of subsequent morbidity. We found that increased density in housing code violations was associated with population-level morbidity independent of poverty, and that the density explained 22 percent of the variation in rates of asthma-related emergency department visits and hospitalizations. Children who had been hospitalized for asthma had 1.84 greater odds of a revisit to the emergency department or a rehospitalization within twelve months if they lived in the highest quartile of housing code violation tracts, compared to those living in the lowest quartile. Integrating housing and health data could highlight at-risk areas and patients for targeted interventions.